Investigating EFL Students’ Speaking Skills Viewed from Self-Efficacy: Instructional Experiences Learned from Seniors High Schools - Setianingsih, Tri; Nafisah, Bq. Zuhrotun; Sumarni, Baiq; Kamarudin, Kamarudin (Journal of Language and Literature Studies, 2024)
This study investigated EFL students’ speaking skills viewed from self-efficacy at seniors high schools. This to measure students’ self-efficacy beliefs and assessments to evaluate their speaking performance to find factors influencing their speaking skills.. The findings of this study had the potential to provide valuable insights into the factors influencing students’ speaking skills development and contribute to the enhancement of language learning and teaching practices, also to find whether there is a relationships between students’ self-efficacy levels and their performance in speaking tasks. A quantitatave approach was employed by using SPSS IBM 26 and qualitative approach was employed by using observation and questionnaires, utilizing surveys, to measure students’ self-efficacy beliefs and assessments to evaluate their speaking performance. The research included 30 second-grade Social Studies students from SMAN 7 Mataram, selected through purposive sampling. A questionnaire with two types of items, totaling 10 questions, was employed as the research tool. The major factors influencing students’ self efficacy at IPS class at SMAN 7 Mataram are social persuasion (50%) and Emotional & Physiological States (50%). The results indicated a strong relationships, with a Pearson correlation coefficient (R) of 0.895, which is considered very high, falling within the 0.80 to 1.000 range. The statistical analysis at a significance level of ? = 0.05 showed a p-value lower than 0.05 (0.000 < 0.05). Thus, the alternative hypothesis (H1) was accepted, and the null hypothesis (H0) was rejected, confirming a significant correlation between students’ self-efficacy and their speaking skills. It means that students need encouragement and support from parents, teachers, and their community to boost their self-efficacy to improve English speaking skills.